Invasive hemodynamic monitoring in the postoperative period of cardiac surgery - Dragosavac,Desanka (1999)
OBJETIVE: To assess the hemodynamic profile of cardiac surgery patients with circulatory instability in the early postoperative period (POP). METHODS: Over a two-year period, 306 patients underwent cardiac surgery. Thirty had hemodynamic instability in the early POP and were monitored with the Swan-Ganz catheter. The following parameters were evaluated: cardiac index (CI), systemic and pulmonary vascular resistance, pulmonary shunt, central venous pressure (CVP), pulmonary capillary wedge pressure (PCWP), oxygen delivery and consumption, use of vasoactive drugs and of circulatory support. RESULTS: Twenty patients had low cardiac index (CI), and 10 had normal or high CI. Systemic vascular resistance was decreased in 11 patients. There was no correlation between oxygen delivery (DO2) and consumption (VO2), p=0.42, and no correlation between CVP and PCWP, p=0.065. Pulmonary vascular resistance was decreased in 15 patients and the pulmonary shunt was increased in 19. Two patients with CI < 2L/min/m² received circulatory support. CONCLUSION: Patients in the POP of cardiac surgery frequently have a mixed shock due to the systemic inflammatory response syndrome (SIRS). Therefore, invasive hemodynamic monitoring is useful in handling blood volume, choice of vasoactive drugs, and indication for circulatory support.